1992
DOI: 10.1111/j.1349-7006.1992.tb02004.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case‐Control Study of Single and Multiple Stomach Cancers in Saitama Prefecture, Japan

Abstract: A case‐control study of stomach cancer was done in Saitama Prefecture, Japan, in relation to dietary, smoking, and drinking habits. The study was based on two sets of cases (216 male single and 35 male multiple stomach cancer cases newly diagnosed and of adenocarcinoma type), and 483 male controls derived from residents of Saitama Prefecture. Dietary habits were investigated for the intake of 12 separate foods and 12 food groups by means of a food frequency questionnaire, including individual taste preferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…One study 29 only stated the finding of a non-statistically significant association in males, and a significant association in females (hazard ratio = 2.54) without providing any further statistical estimates. Two studies 30,31 were later reported in more detail 32,33 , and the more recent publications were used. Four reports were excluded from analysis because tea and coffee were considered combined (OR = 3.2) 34 , coffee assessed as a preference (OR = 1.02) 35 , only cardia cancers (OR = 1.3) 36 were evaluated, or results were presented separately for intestinal (OR = 0.50) and diffuse (OR = 1.98) type gastric cancer using the same control group 37 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study 29 only stated the finding of a non-statistically significant association in males, and a significant association in females (hazard ratio = 2.54) without providing any further statistical estimates. Two studies 30,31 were later reported in more detail 32,33 , and the more recent publications were used. Four reports were excluded from analysis because tea and coffee were considered combined (OR = 3.2) 34 , coffee assessed as a preference (OR = 1.02) 35 , only cardia cancers (OR = 1.3) 36 were evaluated, or results were presented separately for intestinal (OR = 0.50) and diffuse (OR = 1.98) type gastric cancer using the same control group 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies 16,32,33,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58 remained for quantitative data synthesis ( Figure 1 and Table 2). There were 7 cohort studies, with follow-ups ranging from 4.3 to 15 years, and 16 case-control studies, 10 hospital-based, 5 populationbased, and one with no specified study base.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the authors could not analyze types of nuts separately. Moreover, results from four case-control studies investigating the association between nut consumption and gastric cancer are inconclusive [13][14][15][16], and one case-control study found an inverse association between peanut consumption and ESCC risk [17]. Another case-control study observed no association between fruit and nut consumption combined and upper aerodigestive tract cancer risk [18].…”
Section: Introductionmentioning
confidence: 94%